2020
DOI: 10.3389/fphar.2020.584177
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism and Management of Fentanyl-Induced Cough

Abstract: Fentanyl-induced cough (FIC) often occurs after intravenous bolus administration of fentanyl analogs during induction of general anesthesia and analgesia procedure. The cough is generally benign, but sometimes it causes undesirable side effects, including elevated intra-abdominal, intracranial or intraocular pressure. Therefore, understanding the related mechanisms and influencing factors are of great significance to prevent and treat the cough. This paper reviews the molecular mechanism, influencing factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…The exact mechanism of fentanyl-induced cough is still unknown with several hypotheses proposed. 3 One of them suggested that fentanyl activates the μ opioid receptor, which then stimulates the rapidly adapting receptors present on the mucosa of the proximal tracheobronchial airway, causing bronchoconstriction and cough. 3,11 Another hypothesis suggests fentanyl inhibits central sympathetic outflow which stimulates the vagus nerve, producing bronchoconstriction and cough.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The exact mechanism of fentanyl-induced cough is still unknown with several hypotheses proposed. 3 One of them suggested that fentanyl activates the μ opioid receptor, which then stimulates the rapidly adapting receptors present on the mucosa of the proximal tracheobronchial airway, causing bronchoconstriction and cough. 3,11 Another hypothesis suggests fentanyl inhibits central sympathetic outflow which stimulates the vagus nerve, producing bronchoconstriction and cough.…”
Section: Discussionmentioning
confidence: 99%
“…3 One of them suggested that fentanyl activates the μ opioid receptor, which then stimulates the rapidly adapting receptors present on the mucosa of the proximal tracheobronchial airway, causing bronchoconstriction and cough. 3,11 Another hypothesis suggests fentanyl inhibits central sympathetic outflow which stimulates the vagus nerve, producing bronchoconstriction and cough. 3 Therefore, the role of magnesium sulphate in obtunding fentanyl-induced cough was investigated in clinical trials based on its properties as a calcium antagonist and smooth muscle relaxant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations